Improving spare parts management for field services: a model and a case study for the repair kit problem. (24th December 2016) - Saccani, Nicola; Visintin, Filippo; Mansini, Renata; Colombi, Marco
Abstract : The Repair Kit Problem is about determining the stock of service parts carried by field service engineers for on-site product support. Models that optimize cost or service performances have appeared in the literature, but two important managerial decisions have not received enough attention. They are the maximum amount of stock to be carried (referred to as inventory budget) and how often the repair kit should be restocked (replenishment frequency). In this article, we propose a solution method based on the sequential use of optimization and simulation that addresses these issues. The application study was inspired by a real case of an equipment provider and tested on real data. We assess the impact on the overall cost of combinations of inventory budget and replenishment frequency values. Our proposed method aims to improve the managerial understanding of how these decisions interact and to bridge a literature gap. In particular, our method supports managers in (i) defining the Repair Kit to be carried by each Service Engineer; (ii) identifying the levels of inventory budget and replenishment frequency that minimise the overall cost in relation to different combinations of exogenous (cost) parameters.